Return of individual genomic research results within the PRAEGNANT multicenter registry study - Hübner, Hanna; Rübner, Matthias; Kurbacher, Christian; Hadji, Peyman; Hartkopf, Andreas D.; Lux, Michael P.; Huober, Jens; Uhrig, Sabrina; Taran, Florin Andrei; Overkamp, Friedrich; Tesch, Hans; Häberle, Lothar; et al. (Breast Cancer Research and Treatment, 2022)
Purpose: The PRAEGNANT study is a registry study for metastatic breast cancer patients, focusing on biomarker detection. Recently, within this study, genetic alterations in 37 breast cancer predisposition genes were analyzed and genetic findings were detected for 396 participants. The aim of this project was to return genetic results to the physicians and to analyze actions taken (e.g., disclosure of results to patients, validation of results, clinical impact, and impact on the patient’s quality of life) using a questionnaire. Methods: 235 questionnaires were sent out to the study centers, with each questionnaire representing one patient with a genetic finding. The questionnaire consisted of twelve questions in the German language, referring to the disclosure of results, validation of test results, and their impact on treatment decisions and on the patient’s quality of life. Results: 135 (57.5%) questionnaires were completed. Of these, 46 (34.1%) stated that results were returned to the patients. In 80.0% (N = 36) of cases where results were returned, the patient had not been aware of the finding previously. For 27 patients (64.3%), genetic findings had not been validated beforehand. All validation procedures (N = 15) were covered by the patients’ health insurance. For 11 (25.0%) patients, physicians reported that the research results influenced current or future decision-making on treatment, and for 37.8% (N = 17) the results influenced whether family members will be genetically tested. Conclusion: This study provides novel insights into the return of research results and into clinical and personal benefits of disclosure of genetic findings within a German registry.
CRIS-Team Scopus Importer:2022-12-02
Keywords: Breast cancer; Genetic testing; Incidental findings; Research results; Return of results